Akibat Hukum Pelanggaran Legitieme Portie Melalui Akta Wasiat Menurut Burgelijk Wetboek (Studi Kasus Putusan Nomor 3109 K/ PDT/2015) - Fisuda Alifa Mimiamanda Radinda; Ricka Auliaty Fathonah (Fakultas Hukum Universitas Airlangga, 2019)
The purposes of this article are to know the legal consequences if the legitimate rights of Portie's heirs are violated due to the will of the heir. This research is normative legal research particulary prescriptive research. The data research are in the form of primary materials and secondary materials. The technique of collecting legal materials is literature study technique. The approaches in this research are legislation approach and case approach. The conceptual framework is deductive. The results of this article indicate that the legal consequences arising from the violation of the legitimate portie rights are the cancellation of the will. Because the will is deemed defective and should be null and void.